Threshold ratios in retail industry: Basis for setting up cut-offs and standards for investment decision - Nacion, Maria Maan P., Amador, John Ray A., Ortiz, Jhay Zem Y., Solomon, Mario C., Camposano, Alzira Mae S., Mallilin, Kyle Eagi I. 4 0 16; 5
ABSTRACT: The retail industry is continually changing and extremely competitive, providing significant difficulties for industry specialists. According to Noor (2021), setting threshold ratios for liquidity, profitability, solvency, and efficiency is critical in the retail industry's investment choice. The difficulty in developing standard threshold ratios that can be applied uniformly across all investment segments stems from the industry's diversity and intense competition, which necessitate different ratio limits for different segments based on their unique operating characteristics. In this study, the researchers used a descriptive research design. Descriptive statistics such as the mean, mode, and standard deviation are used to describe the characteristics of a 140-person population and to define the threshold ratios in liquidity, profitability, solvency, and efficiency of retailing businesses in Makati Central Business District of Makati City, Philippines, with the help of survey questionnaires to determine accountants, financial managers, and financial analysts' perceptions on what they consider favorable ratios in all areas of financial analysis. Consequently, in terms of liquidity, a current ratio between 2.0 and 2.5 is considered favorable, along with an acid test/quick ratio between 1.75 and 2.0. For profitability, a net profit margin of 3.0% is deemed favorable for highly invested, well-maintained retail stores, while a margin of 5% is suitable for others. Additionally, favorable ratios include a gross profit margin of 50%, a return on assets between 15% and 20%, a return on equity between 10% and 15%, an EBITDA margin of 10%, and an interest coverage ratio of at least 3.00x. In terms of solvency, favorable ratios include a debt-to-equity ratio of 1.00 if the interest coverage ratio is at least 3.00x, otherwise 0.70; an equity ratio of 0.30 if the leverage analysis result is high, otherwise at least 0.50; and a debt ratio of 0.50. Lastly, for efficiency, favorable ratios include asset turnover of 4.00x for low-invested, low-maintained retail stores, fixed asset turnover of 2.5x, equity turnover between 3.1x and 4.0x, accounts receivable turnover of 6.00x, accounts payable turnover of 4.0x, working capital turnover of 6.0x, and inventory turnover between 2.0x and 4.0x. These threshold ratios provide cut-offs and standards, including guidelines for assessing the financial health and performance of retail entities, allowing for more informed investment decision-making. Keywords: Retail industry, threshold ratios, Liquidity, profitability, solvency, efficiency, financial analysis, descriptive research design
Research Paper: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2